2017
DOI: 10.1016/j.mri.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion of the uterine junctional zone in nulliparous and primiparous women assessed by DCE-MRI, as a function of menstrual cycle and hormonal contraception

Abstract: This study provides data on normal perfusion parameters of inner and outer myometrium, which may be potentially useful in assisted reproductive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…A sharp increase in vascularity was seen in the JZ during the follicular phase with a pre-ovulatory peak and a post-ovulatory fall, then another increase at the end of the luteal phase 77 . These findings are in accordance with the DCE-MRI findings 40,41 .…”
Section: Normal Transvaginal Ultrasound Appearancesupporting
confidence: 92%
See 1 more Smart Citation
“…A sharp increase in vascularity was seen in the JZ during the follicular phase with a pre-ovulatory peak and a post-ovulatory fall, then another increase at the end of the luteal phase 77 . These findings are in accordance with the DCE-MRI findings 40,41 .…”
Section: Normal Transvaginal Ultrasound Appearancesupporting
confidence: 92%
“…The suggestion that blood volume, as an extracellular water containing space, could cause the difference in signal intensity between the different uterine layers was not convincingly refuted nor confirmed 23,28 . Signs of reduced water content and increased cell density were also observed by a reduced apparent diffusion coefficient (ADC) in Diffusion Weighted Imaging (DWI) in the junctional zone compared to the outer myometrium 40,41 . The role of blood flow was re-evaluated in more recent and larger studies by dynamic contrast enhanced (DCE) MRI (Table 2) 40,41 Overall, these findings suggest a higher vascular perfusion rate, a higher velocity of tissue blood flow in the capillaries and a greater capillary permeability in the junctional zone than in the outer myometrium (Figure 3B1 and 3B2).…”
Section: Normal Mri Appearancementioning
confidence: 99%
“…It is the dominant pattern in every phase of the menstrual cycle. In accordance with previous data collected from MRI perfusion studies, we observed a trend of more intense enhancement of the myometrium in the follicular and ovulatory phases compared to the luteal phase (911). However, the difference was not statistically significant, perhaps due to the relatively small sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Magnetic resonance imaging (MRI) is an alternative diagnostic method with excellent intrinsic tissue contrast resolution. The uterine anatomy (48) and the perfusion of the myometrium observed on dynamic contrast-enhanced MRI (9,10) have been described in detail in MRI studies.…”
Section: Introductionmentioning
confidence: 99%
“…It seems also that the expression of oxytocin receptors is somewhat dependent on the menstrual cycle with some reports suggesting that the blood flow is higher during the follicular and ovulatory phase compared to the luteal phase [23]. Despite our initial efforts, we could not assess this phenomenon in our study, since we were not able to synchronize the MR-imaging with the menstrual cycle of the women.…”
Section: Discussionmentioning
confidence: 92%